OC-020 Recurrence after radiofrequency ablation for barrett's related high grade dysplasia is due to persistence of epithelial mutations. (28th May 2012) - Zeki, S; Lovat, L; Haidry, R; Barr, H; Shepherd, N; Rodriguez-Justo, M; Wright, N; McDonald, S; Novelli, M
Abstract : Introduction: Radiofrequency ablation (RFA) is a relatively new endoscopic method for ablation of high grade dysplasia (HGD) and intramucosal adenocarcinoma (IMC) in Barrett's oesophagus. Clinical trials have shown enduring eradication of these pathologies. 1 However, some patients develop recurrent dysplasia or cancer. 1 The reason for this is unknown. The aim of the study was to investigate whether this is related to the persistence of known cancer driving mutations after radiofrequency ablation. Methods: Patient records were searched for patients with recurrent HGD or IMC after RFA. Biopsies and endoscopic mucosal resection (EMR) specimens were available before and after RFA for each case. Whole biopsies underwent nested polymerase chain reaction (PCR) sequencing for mutations commonly implicated in progression to adenocarcinoma ( TP53, CDKN2A, K-ras ). Results: Tissue was obtained for six patients before and after RFA. All patients were male (mean age 67 SD±2). Samples from five patients contained detectable mutations. In 3/5 patients, the same mutation was found in material taken before RFA as after (all TP53 mutations). The indication for RFA in all three patients was HGD; two of the patients developed IMC after RFA. In these two cases laser microdissection was performed on the post-RFA EMR samples. PCR revealed the pre RFA mutation to also be present throughout the IMC specimen. Dysplastic tissue adjacent to the IMC contained a mixture of crypts that were either wild type for the mutation in the IMC or contained the mutation indicating that the IMC was a monoclonal outgrowth and that the persistent mutation was driving the development of the recurrence. Furthermore, in all three cases, PCR of a further specimens (performed at a later time point to the first post-RFA EMR), revealed the same mutation as the initial biopsy before RFA, and the first post-RFA EMR. Conclusion: The recurrence of dysplasia and cancer after RFA is likely to be due to failure to remove persistent, cancer driving mutations. Further work will need to be done to assess whether this is because of technical errors, or related to specific problems such as "buried Barrett's". Competing interests: None declared. Reference: 1. Shaheen N, Overholt B, Sampliner RE. Durability of radiofrequency ablation in barrett's esophagus with dysplasia. Gastroenterology 2011;141 :460–8.